Veno-Arterial Extracorporeal Membrane Oxygenation for Patients Undergoing Acute Type A Aortic Dissection Surgery: A Six-Year Experience - Hou, Jun-yi; Wang, Chun-sheng; Lai, Hao; Sun, Yong-xin; Li, Xin; Zheng, Ji-li; Wang, Huan; Luo, Jing-chao; Tu, Guo-wei; Luo, Zhe (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Acute type A aortic dissection (aTAAD) is usually lethal without emergency surgery. Although veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is widely used in patients with cardiogenic shock following cardiac surgery, VA-ECMO support following aTAAD surgery has not been well-described. Based on our 6-year experience, we aimed to retrospectively analyze risk factors, application and timing of VA-ECMO, and outcomes in aTAAD patients. Methods: In this retrospective, single-center study, we enrolled adult patients who underwent aTAAD surgery from January 2014 to December 2019 and were supported with VA-ECMO. Patients were divided into two groups according to whether or not they were successfully weaned from VA-ECMO. Preoperative, intraoperative and postoperative variables were assessed and analyzed. Outcomes of the patients were followed up until discharge. Results: Twenty-seven patients who received aTAAD surgery with VA-ECMO support were included in the study. Nine patients (33.3%) were successfully weaned from VA-ECMO. The median VA-ECMO support time and length of hospital stay in the successfully weaned group were significantly longer than in the group could not be successfully weaned (192 [111–327] vs. 55 [23–95] h, p < 0.01; 29 [18–40] vs. 4 [3–8] days, p < 0.01). Overall in-hospital mortality was 81.5%. The main causes of death were bleeding (37%), neurological complications (15%), and multiple organ dysfunction syndrome (15%). Preoperative levels of creatine kinase-MB (CK-MB) were lower in patients who were successfully weaned from VA-ECMO than in the failed group (14 [6–30] vs. 55 [28–138] U/L, p < 0.01). Postoperative peak levels of CK-MB, cardiac troponin T, lactate dehydrogenase, and lactate were significantly lower in the successful group than in the failed group. Conclusion: Postoperative VA-ECMO support was rarely used in aTAAD patients. Our study showed that VA-ECMO can be considered as a salvage treatment in aTAAD patients, despite the high rate of complications and mortality.